Analysis of Social Media Marketing Strategy Through Instagram in Increasing Consumer Buying Interest in Jjstorecirebon Store - Vivi Luthfiyyah; Moh. Mab’ruri Faozi (Cirebon International Journal of Economics and Business, 2023)
This study aims to find out how the marketing strategy via Instagram has been implemented by Jjstorecirebon Stores to increase consumer buying interest, what obstacles have been faced in implementing the marketing strategy so far at Jjstorecirebon Stores, and which marketing strategies can attract consumers to buy at Jjstorecirebon Stores. This study uses a descriptive research method design using a qualitative approach, namely the observation method and conducting interviews at the research site at the Jjstorecirebon store. The results of the study show that Jjstorecirebon stores apply a marketing strategy to their products using STP (Segmenting, Targeting and Positioning) values. The strategy in the marketing mix applied by Jjstorecirebon Stores is the product strategy for Jjstorecirebon Stores to provide the best and guaranteed product quality, in setting prices on products, adjusting to prices on the market, the promotion strategy carried out by Jjstorecirebon Stores is promoting it through various social media and being in strategic location and easy to reach by consumers. The obstacles faced by jjstorecirebon stores in implementing marketing strategies, namely competition in marketing cosmetic products became tight and some of the cosmetic products sold by jjstorecirebon stores were less attractive to consumers. In attracting consumer buying interest, and experiencing an increase in the implementation of promotional strategies through social media.